2019
DOI: 10.1111/hae.13760
|View full text |Cite
|
Sign up to set email alerts
|

Translation, validation and reliability of the functional capacity questionnaire Haemophilia Activities List for haemophilia patients in Brazil

Abstract: Introduction To date, none of the available assessment instruments to evaluate functional abilities for individuals with haemophilia has been translated and validated in Brazil. Aim To translate, and test the construct validity, internal consistency and the reliability of the Haemophilia Activities List (HAL) for the Brazilian population with severe and moderate haemophilia (type A or B) and to investigate differences in the self‐perception of functional abilities in patients adults with haemophilia classified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…The ICC values of the present study are similar to previously reported ICC values of 0.87–0.97 in adult PWH in the USA ( n = 158–162), which reported on two questionnaires completed within 2 hours 15 . ICC values (0.66–0.90) were lower in Brazilian PWH ( n = 52) who completed the HAL during interviews (with an interval of 15 days), which is different to individually completing a paper questionnaire in the present study 16 . SEM and SDC values have not been published until now.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The ICC values of the present study are similar to previously reported ICC values of 0.87–0.97 in adult PWH in the USA ( n = 158–162), which reported on two questionnaires completed within 2 hours 15 . ICC values (0.66–0.90) were lower in Brazilian PWH ( n = 52) who completed the HAL during interviews (with an interval of 15 days), which is different to individually completing a paper questionnaire in the present study 16 . SEM and SDC values have not been published until now.…”
Section: Discussionsupporting
confidence: 86%
“…which is different to individually completing a paper questionnaire in the present study. 16 SEM and SDC values have not been published until now.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the data may not be representative for the entire US population. The HAL scores in the current data (median HAL sum: 65.0) were comparable to HAL scores in PWH from Jamaica (median: 66.1) and Brazil (weighted mean: 66.4), but lower than HAL scores in PWH from the United Kingdom (median: 80) and the Netherlands (median: 96) 18–21 . In Sweden, PWH with a later onset of treatment showed a median HAL sum score of 56, compared to a median of 98 in PWH with early treatment 22 .…”
Section: Discussionsupporting
confidence: 51%
“…In addition, some items in the domains ‘self‐care’, ‘household tasks’ and ‘leisure activities and sports’ have been reported as inappropriate in Jamaican and Indian studies 5,18 . After the stepwise procedure some of these culturally dependent items were removed, while others were still included in the HAL short (playing games, sports, putting on socks and shoes, going on a holiday [active]) because the items were appropriate for most populations 2,19,23–25 . Based on cross‐cultural validation studies and the current study population, the HAL short includes most relevant and informative items for PWH with access to intensive treatment 2,19,23,24 .…”
Section: Discussionmentioning
confidence: 99%